Power Mechanics Curriculum Guide. Curriculum Development. Bulletin 1813 - Territo, Peter A., Jr; McMurry, James G (1987)
This model instructional unit was developed to aid trade and industrial education teachers in Louisiana in preparing students for careers in the field of power mechanics. Students are provided experiences related to the design, theory, construction, and appropriate uses of the power systems, as well as the maintenance and repair of the more common industrial power systems. The guide provides model performance objectives, current technology content, sources, and lists of supplemental materials. Following a course description and rationale, the guide contains 11 instructional units covering the following topics: introduction; safety; tools and equipment; mechanical power systems; external combustion engines; internal combustion engines; fluid power systems; electrical power systems; automated systems and robotics; careers; and special projects. Each unit consists of introduction; competencies; general performance objectives/goals; specific performance objectives and mastery criteria; methodology; suggested interest approaches; unit outline; subject-matter content related to specific performance objectives and learning activities; activity sheets; transparency masters; test with answer key; evaluation and testing methods; and equipment and supply list. (KC)